Land grab or development opportunity? International farmland deals in Africa - Lorenzo Cotula (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective discusses the increasing number and size of large-scale farmland acquisitions in Africa by foreign investors over the past five years, including the opportunities and risks created by this trend.
Keywords: 330